2020
DOI: 10.3791/61481
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Spontaneous Ca<sup>2+</sup> Fluxes and their Downstream Effects in Primary Mouse Midbrain Neurons

Abstract: Parkinson's disease (PD) is a devastating neurodegenerative disorder caused by the degeneration of dopaminergic (DA) neurons. Excessive Ca 2+ influx due to the abnormal activation of glutamate receptors results in DA excitotoxicity and has been identified as an important mechanism for DA neuron loss. In this study, we isolate, dissociate, and culture midbrain neurons from the mouse ventral mesencephalon (VM) of ED14 mouse embryos. We then infect the long-term primary mouse midbrain cultures with an adeno-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Immunostaining showed that midbrain cultures contain mature NeuN + neurons that are either TH + or TH - (Fig. 2B) (Bancroft & Srinivasan, 2020;Srinivasan et al, 2016;Zarate et al, 2020). These neurons are co-cultured with primary midbrain astrocytes expressing S100B (Fig.…”
Section: Th + and Thneurons From Primary Mouse Midbrain Cultures Showmentioning
confidence: 93%
See 4 more Smart Citations
“…Immunostaining showed that midbrain cultures contain mature NeuN + neurons that are either TH + or TH - (Fig. 2B) (Bancroft & Srinivasan, 2020;Srinivasan et al, 2016;Zarate et al, 2020). These neurons are co-cultured with primary midbrain astrocytes expressing S100B (Fig.…”
Section: Th + and Thneurons From Primary Mouse Midbrain Cultures Showmentioning
confidence: 93%
“…Both TH + and THneurons exhibited robust spontaneous Ca 2+ fluxes with heterogenous frequencies and amplitudes ( Fig. 2D and supplementary movie 1) (Bancroft & Srinivasan, 2020).…”
Section: Th + and Thneurons From Primary Mouse Midbrain Cultures Showmentioning
confidence: 95%
See 3 more Smart Citations